Does Involvement of Local NGOs Enhance Public Service Delivery? Cautionary Evidence from a Malaria-Prevention Evaluation in India - Das, Ashis; Friedman, Jed; Kandpal, Eeshani (World Bank, Washington, DC, 2014)
Using data from an experimental supportive intervention to India's malaria control program, this paper studies the impact of leveraging local non-state capacity to promote mosquito net usage and recommended fever care-seeking patterns. The supportive activities were conducted simultaneously by three nongovernmental organizations in two endemic districts in the state of Orissa. The study finds that program impact varied significantly by location. Examining three potential sources of this variation (differential population characteristics, differential health worker characteristics, and differential implementer characteristics), the analysis provides evidence that both population and nongovernmental organization characteristics significantly affected the success of the program. The paper discusses these findings as they relate to the external validity of development policy evaluations and, specifically, for the ability of the health system to benefit from limited non-state capacity in under-resourced areas.